MEMAHAMI KETERKAITAN ANTARA LINGKUNGAN KERJA NON FISIK DAN LOYALITAS KERJA PADA GENERASI Z - Panggabean, Tracy Fransiska; Satwika, Pratista Arya (Jurnal Psikologi : Media Ilmiah Psikologi, 2024)
Generation Z has a significantly lower work loyalty level than other generations. One of the reasons for the decline in their loyalty is the non-physical work environment, which includes harmonious relationships among colleagues, superiors, and subordinates. This study aims to investigate the influence of the non-physical work environment on the level of work loyalty among Generation Z employees known to have low work loyalty. The non-probability sampling method with purposive sampling technique was used in this study, with 138 participants who met the research criteria. Two types of measurement instruments, namely the work loyalty scale and the non-physical work environment scale, were applied in this study. The results of the analysis using the non-parametric Spearman correlation test showed a significant influence between the non-physical work environment and work loyalty. The identified positive relationship indicates that improving the non-physical work environment can be an effective strategy to enhance the loyalty of Generation Z employees. This finding has important implications for organizations to pay attention to and enhance the non-physical work environment to strengthen employee loyalty